2022
DOI: 10.1080/21645515.2022.2050121
|View full text |Cite
|
Sign up to set email alerts
|

A matter of trust: a qualitative comparison of the determinants of COVID-19 vaccine hesitancy in Taiwan, the United States, the Netherlands, and Haiti

Abstract: COVID-19 vaccination is an effective intervention preventing individuals from contracting SARS-CoV-2 or transmitting the virus to others. However, in many countries, vaccine hesitancy has impeded the progress of mass vaccination to reach herd immunity. This study aimed to understand the similarities and differences in the determinants of COVID-19 vaccine hesitancy in Taiwan, the United States, the Netherlands, and Haiti. A qualitative study was conducted by face-to-face interviews with participants in Taiwan a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 26 publications
1
10
0
Order By: Relevance
“… 22 , 69 While some studies have shown that that lack of information and misinformation about COVID-19 vaccines lead to vaccine refusal (see ref. 12 , 14 our generally vaccine-accepting participants were distrustful of shifts in messages and guidelines about the vaccines even when delivered by trustworthy sources (e.g., public health officials and official agencies). Given the frequency in which earlier messages (e.g., get the first vaccine offered, keep the same brand of vaccine for both doses) were communicated, the changes to guidance were not explained with the same level of frequency to override people’s original understanding.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“… 22 , 69 While some studies have shown that that lack of information and misinformation about COVID-19 vaccines lead to vaccine refusal (see ref. 12 , 14 our generally vaccine-accepting participants were distrustful of shifts in messages and guidelines about the vaccines even when delivered by trustworthy sources (e.g., public health officials and official agencies). Given the frequency in which earlier messages (e.g., get the first vaccine offered, keep the same brand of vaccine for both doses) were communicated, the changes to guidance were not explained with the same level of frequency to override people’s original understanding.…”
Section: Discussionmentioning
confidence: 98%
“… 12–14 and Asia (see ref. 14 found that a people who perceive the risk of COVID-19 as low tend to reject COVID-19 vaccines. However, we found that our participants perceived the risk of COVID-19 as high but consider COVID-19 vaccines as being riskier.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This study also found VH to be higher among African-Americans (34%), Hispanics (29%), those who had children at home (25%), rural dwellers (29%), people in the northeastern US (25%), and those who identified as Republicans (29%). Several studies determine that trust on COVID-19 vaccine (Wang et al 2022), healthcare workers, healthcare system, science, and policymakers who design vaccination strategies, are important factors in reducing VH. This mistrust is due to misinformation and rumors.…”
Section: Literature Reviewmentioning
confidence: 99%